2018
DOI: 10.3892/etm.2018.5746
|View full text |Cite
|
Sign up to set email alerts
|

Optimal method of gold nanoparticle administration in melanoma‑bearing mice

Abstract: Abstract. The present study assessed different methods of administering gold nanoparticles (GNPs) using different formulations to determine which of the methods achieved optimal radiosensitization. Cells from the B16F10 mouse melanoma cell line were implanted in the femoral area of mice, assigned to one of the eight following groups: i) Control; ii) intravenous (IV) injection of polyethylene glycol (PEG)-binding GNPs (Peg-GNPs) alone; iii) direct intratumoral (IT) injection of Peg-GNPs alone; iv) radiotherapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This is in line with the recent data showing that 1 mg/kg AuNPs might be around the real therapeutical dose. 25 , 36 , 37 BSA-AuNPs are considered a safe platform among various AuNPs types, nevertheless, their biocompatibility still needs to be carefully assessed. In one of the recent publications, five different doses of AuNPs coated with BSA ranging from 1.16 mg/kg to 5.84 mg/kg were tested for 8 consecutive days after intravenous injections in mice.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the recent data showing that 1 mg/kg AuNPs might be around the real therapeutical dose. 25 , 36 , 37 BSA-AuNPs are considered a safe platform among various AuNPs types, nevertheless, their biocompatibility still needs to be carefully assessed. In one of the recent publications, five different doses of AuNPs coated with BSA ranging from 1.16 mg/kg to 5.84 mg/kg were tested for 8 consecutive days after intravenous injections in mice.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests a synergistic effect between the nanoparticles and EBRT. Based on these results, we suggest that a combination of nanoparticles and EBRT is appropriate for inhibiting the growth of melanoma tumours [ 13 , 14 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“… 50 Anijdan et al found that tumor growth was partially inhibited, albeit without a statistically significant survival benefit, following intratumoral injection of AuNPs (~500–1000 μg) under X-ray irradiation at 20 Gy. 51 The study by Komatsu et al 52 demonstrated regardless of intravenous administration or intratumoral injection of AuNPs (400 μg), X-ray irradiation at 10 Gy showed no tumor inhibition or statistical survival benefit. In our study, intratumoral injection of mAuNPs (280 μg) combined with carbon ion irradiation at 4 Gy contributed to a significant radiation enhancement of 94% in tumor growth inhibition and a significant 75% improvement in survival time.…”
Section: Discussionmentioning
confidence: 99%